Role of Immunological Method of Fecal Occult Blood Test for Screening Colorectal Diseases - Farida Yeasmin (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Background: Colorectal diseases specially colorectal carcinoma is one of the major health problems throughout the world. Therefore, early diagnosis of these diseases is mandatory. There are various screening methods are used for early diagnosis of colorectal diseases. Among them fecal occult blood test is the most widely used screening test.